Quality of life in chronic heart failure: cilazapril and captopril versus placebo. Issue 6 (1st June 1998) - Bulpitt, C J; Fletcher, A E; Dössegger, L; Neiss, A; Nielsen, T; Viergutz, S
Abstract : Objective: To measure quality of life (QOL) in patients with mild to moderate heart failure treated with angiotensin converting enzyme (ACE) inhibitors cilazapril or captopril. Design: Randomised, double blind, placebo controlled, parallel groups trial. Subjects: 367 patients with New York Heart Association (NYHA) heart failure class II (62%), III (36%) or IV (1%). Methods: Patients were randomised to receive cilazapril 1 mg daily (n = 191) or captopril 25 mg three times daily (n = 90) for 24 weeks, or placebo for 12 weeks followed by cilazapril 1 mg daily for a further 12 weeks (n = 86). If patients had not responded after four weeks cilazapril was increased to 2.5 mg daily and captopril to 50 mg three times daily. QOL was assessed at baseline, 12, and 24 weeks using the sickness impact profile (SIP), the profile of mood states (POMS), the Mahler index of dyspnoea-fatigue, and a health status index (HSI). Results: The physical dimension of the SIP averaged 7 units at baseline and improved after 12 weeks by 2.24 units in the cilazapril group, 2.38 units in the captopril group, and 1.51 units in the placebo group. The difference between drug and placebo was therefore 0.73 units (95% CI −0.86 to 2.32) for cilazapril, and 0.87 units (95% CI −0.96 to 2.70) for captopril, with small non-significant effect sizes (a statistical method for estimating the importance of a treatment related change) of 0.12 and 0.14. Similar results were observed for the total POMS and HSI scores. Although QOL improved more on the ACE inhibitors than on placebo, the effect sizes were not significant (⩽ 0.26). Conclusions: Improvements in QOL in mild to moderate heart failure were small when treated with cilazapril or captopril compared with placebo.